Drought-triggered repression of miR166 promotes drought tolerance in soybean - Chen Zhao; Jingjing Ma; Chen Yan; Yu Jiang; Yaohua Zhang; Yudan Lu; Ye Zhang; Suxin Yang; Xianzhong Feng; Jun Yan (Crop Journal, 2024)
Drought stress limits agricultural productivity worldwide. Identifying and characterizing genetic components of drought stress-tolerance networks may improve crop resistance to drought stress. We show that the regulatory module formed by miR166 and its target gene, ATHB14-LIKE, functions in the regulation of drought tolerance in soybean (Glycine max). Drought stress represses the accumulation of miR166, leading to upregulation of its target genes. Optimal knockdown of miR166 in the stable transgenic line GmSTTM166 conferred drought tolerance without affecting yield. Expression of ABA signaling pathway genes was regulated by the miR166-mediated regulatory pathway, and ATHB14-LIKE directly activates some of these genes. There is a feedback regulation between ATHB14-LIKE and MIR166 genes, and ATHB14-LIKE inhibits MIR166 expression. These findings reveal that drought-triggered regulation of the miR166-mediated regulatory pathway increases plants drought resistance, providing new insights into drought stress regulatory network in soybean.